Efek Residu Media Tanam dengan Penambahan Kompos Secara Berulang Terhadap Pertumbuhan dan Serapan Hara Nitrogen Tanaman Kailan - Anis Sholihah; Agus Sugianto (Universitas Islam Malang, 2022)
This study aims to determine the potential of planting media residues from rice crop residues in the second planting period which were given input of a mixture of kiapu compost and straw with various compositions with the indicator plant used was kailan which belongs to the potential vegetable group and has a fairly high nutritional value. The study used a randomized block design with treatments consisting of 5 compost mixtures and 2 comparison treatments, namely pearl NPK fertilizer treatment and control so the treatment was as follows; M0 : control, M1 : 100% kiapu, M2 : 75% kiapu + 25% rice straw, M3 : 50% kiapu + 50% rice straw, M4 : 25% kiapu + 75% rice straw, M5 : 100% straw and M6 : NPK. The results showed that repeated application of the compost mixture was able to give a positive residual effect so that it could increase growth, yield and N uptake in kailan plants. The increase in plant length due to the addition of repeated compost ranged from 1.96% to 22.79%, leaf area ranged from 11.28% to 75.63% and total plant fresh weight ranged from 28.85% to 59.94%. The treatment with compost significantly increased root N uptake, canopy N uptake and total N uptake compared to control, ranging from 223.67% to 283.36% at root N uptake, 175.03% to 232.47% at canopy N uptake and 194, 43% to 241.63% on the total N uptake of plants.